English Error Analysis Of Written English Of Chinese Students In A Malaysian Secondary School: A Case Study - Lim, Margery Phek Chu (1994)
The objectives of this study were to identify the written errors produced by a group of Chinese learners of English as a second language, trace the sources of these errors and offer plausible explanantions for their occurrence.